Ribosomal DNA copy number associated with blood metal levels in school-age children: A follow-up study on a municipal waste incinerator in Zhejiang, China. (November 2022) - Xu, Peiwei; Feng, Lingfang; Xu, Dandan; Wu, Lizhi; Chen, Yuan; Xiang, Jie; Cheng, Ping; Wang, Xiaofeng; Lou, Jianlin; Tang, Jun; Lou, Xiaoming; Chen, Zhijian
Abstract: To evaluate the body burdens of heavy metals and explore the impact of environmental metal exposure on ribosomal DNA (rDNA) or mitochondrial DNA (mtDNA) copy number (CN) variation in school-age children living near a municipal waste incinerator (MWI), we conducted a follow-up study in 2019. A total of 146 sixth-grade children from a primary school located 1.2 km away from the MWI were recruited for our study. Metals, including vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), selenium (Se), cadmium (Cd), stannum (Sn), stibium (Sb), thallium (Tl), and lead (Pb), were determined by an inductively coupled plasma mass spectrometer method. Real-time qPCR was used to measure the rDNA and mtDNA CN. The blood metal levels followed this order: Zn > Cu > Se > Pb > Mn > Sb > As > Ni > Cd > Co > Cr > Sn > V > Tl. Blood Cr level was significantly correlated with 18 S, 2.5 S, and 45 S CN (β = −0.25, −0.22, −0.26, p  < 0.05); Ni was correlated with 5 S (β = −0.36, p  < 0.01); Cu was correlated with 28 S, 18 S, and 5.8 S (β = −0.24, −0.24, −0.23, p  < 0.05); while Zn was correlated with 18 S, 5.8 S, and 45 S (β = −0.28, −0.32, −0.26, p  < 0.05). In conclusion, school-age children living near the MWI had lower blood metal levels compared to children recruited in 2013, while rDNA CN loss was found to be correlated to several heavy metals in these children. Graphical abstract: Image 1 Highlights: Children living around MWIs may not suffer considerable long-term accumulation of heavy metals. Blood Cr was correlated with 18 S, 2.5 S, and 45 S CN. Blood Cu was correlated with 28 S, 18 S, and 5.8 S CN. Blood Zn was correlated with 18 S, 5.8 S, and 45 S CN.